Kesulitan Pembelajar Bahasa Asing Indonesia (BIPA) dalam Mempelajari BIPA - Adwitya Widya Dhari; Syafryadin (Universitas Negeri Surabaya, 2025)
The Subject of this study is the difficulties confronted by the Indonesian foreign language learners (BIPA) that taught by postgraduate English Education students at University of Bengkulu. Data collection involves a total of 20 participants aged from 19 to 63 years who attended six to seven online sessions conducted by postgraduate students in their third semester, with a quantitative research method. Participants were assessed for their experience and hardships via a questionnaire regarding how they were challenged by the learning setting out alongside pronunciation, vocabulary, grammar, cultural barriers, and lack of time practicing. It came out that out of the challenges the students encountered vocabulary and averages were the most fundamental problems together with pronunciation, grammar, cultural differences, and insufficient time to practice speaking. This is consistent with the literature on the subject of cultural and psychological variables working in combination with linguistic factors learning in a virtual environment. The conclusion reached in the study is that to deal with the above problems better teaching strategies such as the use of technology, culture, and practice are needed.